KONTRIBUSI RETRIBUSI PELAYANAN KESEHATAN GIGI DAN MULUT TERHADAP PENDAPATAN ASLI DAERAH PROVINSI SULAWESI SELATAN - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2012)
This study aims to find out the contribution Levy Dental and Oral Health Services for Revenue of South Sulawesi province in 2006-2010 and to determine the trend of the development contribution levies Dental and Oral Health Services 2006-2010. The analytical method used is the method of contribution and trend analysis. From the results of this study indicate bahawa number of cases handled by the Center for Dental and Oral Health Services of South Sulawesi province has decreased from 2006 to 2008 while in 2009 through 2010 has increased. Acceptance fee of oral health services from 2006 to 2008 has decreased while in 2009 until the year 2010 has increased. Levy contribution of oral health services to the revenue (PAD) at the Center for Dental and Oral Health Services of South Sulawesi province from 2006 until 2010 relafif still very small at less than 1%, that number also fluctuated from year to year due to number of cases handled by the amount of fluctuation. Trend development contribution levy of oral health services at the Center for Dental and Oral Health Services of South Sulawesi province is a kind of a positive trend, so that if the value of X increases, the value of Y, the contribution levy of oral health services is also increasing but the increase is not too significant .